2011
DOI: 10.1089/cbr.2010.0907
|View full text |Cite
|
Sign up to set email alerts
|

Beta Androstenediol Mitigates the Damage of 1 GeV/n Fe Ion Particle Radiation to the Hematopoietic System

Abstract: Space exploration is associated with exposure to 1-3 Gy solar particle radiation and galactic cosmic radiation that could increase cancer rates. Effective nontoxic countermeasures to high linear energy transfer (LET) radiation exposure are highly desirable but currently not available. The aim was to determine whether a single subcutaneous injection of androstenediol (D 5 androsten-3b, 17b-diol [AED]) could mitigate and restore the mouse hematopoetic system from the radiation-mediated injury of 3 Gy whole-bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In a previous study, we found 56 Fe dose-dependent decreases in blood WBCs and in all three major leukocyte types on Day 4 post-irradiation, followed by complete recovery in cell numbers by Day 113; monocyte–macrophage percentages, however, were significantly decreased in both blood and spleen [ 36 ]. Others have also noted great reduction in WBCs and the three major leukocyte types in mice during 4, 7 and 14 days after 3 Gy 56 Fe irradiation [ 47 ]. This latter study also demonstrated that subcutaneous injection of androstenediol 30 min after exposure could significantly mitigate the detrimental effect.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we found 56 Fe dose-dependent decreases in blood WBCs and in all three major leukocyte types on Day 4 post-irradiation, followed by complete recovery in cell numbers by Day 113; monocyte–macrophage percentages, however, were significantly decreased in both blood and spleen [ 36 ]. Others have also noted great reduction in WBCs and the three major leukocyte types in mice during 4, 7 and 14 days after 3 Gy 56 Fe irradiation [ 47 ]. This latter study also demonstrated that subcutaneous injection of androstenediol 30 min after exposure could significantly mitigate the detrimental effect.…”
Section: Discussionmentioning
confidence: 99%